(untitled) (Mediscope, 2021)
Objectives: To observe the palmar dermatoglyphic patterns of β thalassemia major patients. Methods: This cross-sectional type of analytical study was performed in the Department of Anatomy, Sir Sallimullah Medical College, Dhaka between the periods of January 2016 to December 2016. 55 β thalassemia major patients aged between (5-35) years were considered as case group and 55 healthy individuals of the same age & sex were considered as control group in this study. The palmar dermatoglyphic patterns and Total Finger Ridge count (TFRC) on the distal phalanges of the β thalassemia major patients were observed and compared with healthy individuals. Results: The palmar dermatoglyphic patterns were significantly different between the two groups (p > 0.05). The mean (±SD) of Total Finger Ridge count (TFRC) were higher in β thalassemia major patients in comparison to the healthy individuals. Conclusion: This study concludes that, palmar dermatoglyphic has a diagnostic value for β thalassemia major patients. Mediscope 2021;8(2): 94-102